Evaluation of maggot therapy applied to four clinical cases of animals in Bogota (Colombia) (2010)
The use of Lucilia sericata larvae in the treatment of infected wounds in four animal cases was evaluated. We used two bovines, one horse and one canine treated with maggot therapy in the veterinary clinic of the University of La Salle, Bogotá-Colombia. We developed the protocol for disinfection of the embrionic eggs of L. sericata. After eclosion, aseptic first instars were placed on the animal wounds, and these were covered with bandages. The macroscopic evaluation of the wounds, based on a standardized test, allowed us to assign for the variables of odor, presence of exudate and inflammation, the optimal scores at nine and 12 days treatment, while for the new granulation tissue the best rating was established on day nine. The action of the larvae on the wounds produced the removal of the necrotic tissue, control of infection and the formation of renewed granulation tissue, all leading to the healing of the lesions in the animals in a maximum of 15 days. The effectiveness of L. sericata larvae in the treatment of infected animal wounds was demonstrated. Based on this, maggot therapy is presented as an effective alternative for the treatment of wounds in diverse animal species.